A new dynamic in vitro modular capillaries-venules modular system: Cerebrovascular physiology in a box - Cucullo, Luca (BioMed Central, 2013)
BACKGROUND: The study of the cerebrovascular physiology is crucial to understand the pathogenesis of neurological disease and the pharmacokinetic of drugs. Appropriate models in vitro often fail to represent in vivo physiology. To address these issues we propose the use of a novel artificial vascular system that closely mimics capillary and venous segments of human cerebrovasculature while also allowing for an extensive control of the experimental variables and their manipulation. RESULTS: Using hollow fiber technology, we modified an existing dynamic artificial model of the blood–brain barrier (BBB) (DIV-capillary) to encompass the distal post-capillary (DIV-venules) segments of the brain circulatory system. This artificial brain vascular system is comprised of a BBB module serially connected to a venule segment. A pump generates a pulsatile flow with arterial pressure feeding the system. The perfusate of the capillary module achieves levels of shear stress, pressure, and flow rate comparable to what observed in situ. Endothelial cell exposure to flow and abluminal astrocytic stimuli allowed for the formation of a highly selective capillary BBB with a trans-endothelial electrical resistance (TEER; >700 ohm cm(2)) and sucrose permeability (< 1X10(-u) cm/sec) comparable to in vivo. The venule module, which attempted to reproduce features of the hemodynamic microenvironment of venules, was perfused by media resulting in shear stress and intraluminal pressure levels lower than those found in capillaries. Because of altered cellular and hemodynamic factors, venule segments present a less stringent vascular bed (TEER <250 Ohm cm(2); P(sucrose) > 1X10(-4) cm/sec) than that of the BBB. Abluminal human brain vascular smooth muscle cells were used to reproduce the venular abluminal cell composition. CONCLUSION: The unique characteristics afforded by the DIV-BBB in combination with a venule segment will realistically expand our ability to dissect and study the physiological and functional behavior of distinct segments of the human cerebrovascular network.